Решить уравнение: (X-3)^2+(x+4)^2-(x-5)^2=17x+24

Решить уравнение: (X-3)^2+(x+4)^2-(x-5)^2=17x+24
Гость
Ответ(ы) на вопрос:
Гость
[latex](x-3)^2+(x+4)^2-(x-5)^2=17x+24 \\\ x^2-6x+9+x^2+8x+16-x^2+10x-25-17x-24=0 \\\ x^2-5x-24=0 \\\ D=25+4\cdot24=121 \\\ x_1= \frac{5+11}{2}=8 \\\ x_1= \frac{5-11}{2}=-3[/latex] Ответ: 8 и -3
Гость
x^2 -6x+9+x^2+8x+16 -x^2+10x-25-17x-24 =0 x^2 -5x -24 =0 D = 25 -4(-24) =Y121;  D=11 x1= (5+11)/2 =8 x2 =(5-11)/2 = -3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы